Islam di Asia Tenggara - Rahmawati Rahmawati (Rihlah : Jurnal Sejarah dan Kebudayaan, 2014)
Islam came and berkembangan in Southeast Asia has a process with a wide range of channels in its spread, such as through trade channels, channel marriage, Sufism channels, educational channels, line art and political channels, but Islam is a religion that inspired the Alqurani so easy diterimah by community local. Overall the history of Muslims in Southeast Asia has led to struggle once articulation and assimilation with the local culture, so as to produce a new culture that is dynamic and unique, a liberal civilization of Southeast Asia. With the acceptance of Islam in peace then, as well as the development of Islamic civilization in its various aspects Therefore, Southeast Asia is a struggle field, as well as acculturation and assimilation of local culture, as well as among local cultural sesame. Therefore in Asia Tenggaralah live and develop various religious systems.